2006
DOI: 10.1016/j.jeconom.2005.06.019
|View full text |Cite
|
Sign up to set email alerts
|

Generalized spectral tests for the martingale difference hypothesis

Abstract: This article proposes a test for the martingale difference hypothesis (MDH) using dependence measures related to the characteristic function. The MDH typically has been tested using the sample autocorrelations or in the spectral domain using the periodogram. Tests based on these statistics are inconsistent against uncorrelated non-martingales processes. Here, we generalize the spectral test of Durlauf (1991) for testing the MDH taking into account linear and nonlinear dependence. Our test considers dependence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
170
1
9

Year Published

2006
2006
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 185 publications
(195 citation statements)
references
References 46 publications
7
170
1
9
Order By: Relevance
“…Moreover, it can be shown that under mild assumptions our test based on D 2 n is asymptotically admissible, that is, there does not exist a test that is uniformly more powerful than our test for a general class of local alternatives to H 0 , see Corollary 4 in Escanciano and Velasco (2006). Thus, the test proposed in this paper should be viewed not as competing with but as a complement to that considered in Escanciano and Velasco (2006) since they have different power properties and both are asymptotically admissible.…”
Section: Corollary 4 Under (1) and Assumption A1mentioning
confidence: 98%
See 4 more Smart Citations
“…Moreover, it can be shown that under mild assumptions our test based on D 2 n is asymptotically admissible, that is, there does not exist a test that is uniformly more powerful than our test for a general class of local alternatives to H 0 , see Corollary 4 in Escanciano and Velasco (2006). Thus, the test proposed in this paper should be viewed not as competing with but as a complement to that considered in Escanciano and Velasco (2006) since they have different power properties and both are asymptotically admissible.…”
Section: Corollary 4 Under (1) and Assumption A1mentioning
confidence: 98%
“…Hong's (1999) approach involves the choice of a kernel, a bandwidth parameter and an integrating measure and, in general, statistical inferences are not robust to these choices. Escanciano and Velasco (2006) avoid bandwidth choices by means of a generalized spectral distribution function. In this paper we propose a MDH test which preserves the good properties of Escanciano and Velasco's (2006) test and that complements it because it leads to different power properties.…”
Section: E (Y T − ) F (I T−1 ) = 0 ∀F (·) ⇐⇒ E (Y T − ) W (I T−1 X)mentioning
confidence: 99%
See 3 more Smart Citations